2020
DOI: 10.30699/jambs.28.127.105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Phenylalanine Arginine Beta Naphthylamide (PAβN) and Curcumin on Minimum Inhibitory Concentration of Aminoglycosides on Pseudomonas aeruginosa Clinical Isolates

Abstract: Background & Objective: Efflux pump inhibitors (EPIs) can block efflux pumps and are helpful in potentiating the activity of aminoglycosides against Pseudomonas aeruginosa. The present study compared the effects of phenylalanine-arginine beta naphthylamide (PAβN) and curcumin on aminoglycoside minimum inhibitory concentration (MIC) on Pseudomonas aeruginosa clinical isolates. Materials & Methods: For this descriptive-analytical study, 100 clinical isolates of Pseudomonas aeruginosa were collected and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…There are different strategies that inhibit efflux pumps: (1) develop new antibiotics that are not affected by efflux pumps; (2) change the function of efflux pumps through structural modifications; (3) inhibit the energy sources needed to operate efflux pumps; (4) decrease the expression of efflux pump genes; and (5) competitively/non-competitively inhibit efflux pumps [ 62 ]. By testing a resistant strain that is susceptible to the antibiotic, in vitro experiments have elucidated that EPIs can restore the efficacy of an antibiotic and reduce the Minimum Inhibitory Concentrations (MICs) of antibiotics and the opportunities for resistant growth when associated with the antibiotics [ 61 , 62 , 63 ].…”
Section: Secondary Metabolites Production Of Plants As Potential Epismentioning
confidence: 99%
See 1 more Smart Citation
“…There are different strategies that inhibit efflux pumps: (1) develop new antibiotics that are not affected by efflux pumps; (2) change the function of efflux pumps through structural modifications; (3) inhibit the energy sources needed to operate efflux pumps; (4) decrease the expression of efflux pump genes; and (5) competitively/non-competitively inhibit efflux pumps [ 62 ]. By testing a resistant strain that is susceptible to the antibiotic, in vitro experiments have elucidated that EPIs can restore the efficacy of an antibiotic and reduce the Minimum Inhibitory Concentrations (MICs) of antibiotics and the opportunities for resistant growth when associated with the antibiotics [ 61 , 62 , 63 ].…”
Section: Secondary Metabolites Production Of Plants As Potential Epismentioning
confidence: 99%
“…In Vietnam, P. vittata and some other ferns have been used to remedy metal-contaminated soil in the Thai Nguyen mine with plants [ 22 , 71 , 72 ]. In 1999, Singh et al reported that a decoction of Pteris vittata was effective in the treatment of dysentery [ 63 ]. In 2008, Singh et al also showed that this fern contains rutin, which is known to have the ability to fight microorganisms that cause gastrointestinal diseases [ 64 ].…”
Section: Secondary Metabolites Production Of Plants As Potential Epismentioning
confidence: 99%